LESSON STUDY PENERAPAN MODEL PEMBELAJAJARAN KOOPERATIF PADA MATA PELAJARAN PPKn DI MAN 2 MODEL MATARAM - Yuliatin Yuliatin; Muh Zubair; Bagdawansyah Alqadri (Jurusan P. IPS, FKIP, Universitas Mataram, 2022)
The purpose of this study was to improve the quality of Civics learning through the implementation of Lesson Study implementation of cooperative learning model in MAN 2 Mataram Model. This study uses a descriptive qualitative approach, because the main concern of this study is to analyze the implementation of Lesson Study. The outputs of this research are scientific articles and PPKn learning tools in the form of lesson plans and learning media. Collecting data in this study using interview, observation, and documentation techniques. Furthermore, the data obtained were analyzed qualitatively with the steps of data reduction, data presentation, and drawing conclusions. The results showed that the Lesson Study of the application of the cooperative learning model in Civics subjects at MAN 2 Mataram Model had been carried out for 3 cycles. Each cycle consists of three activities, namely: (1) planning, (2) implementation, and (3) reflection. In cycle 1, the planning carried out was the reconstruction of the lesson plans for class XI in the first semester, the main material: basic concepts of obligations and human rights by integrating cooperative learning models of a combination of Talking Stick and Snowball Throwing types, as well as developing PowerPoint media. At the time of implementation, the model teacher was the PPKn teacher at the school. Meanwhile, the research team acted as observers. The results of cycle 1 reflections show that there are positive things that must be maintained, among others, PowerPoint media that is attractive and easy to understand and a pleasant classroom atmosphere. However, there are also other things that must be improved, namely the existence of learning activities that are not carried out according to the lesson plan. In class 2, the planning carried out was the reconstruction of the lesson plans for class XI semester I, the main material: the substance of obligations and human rights in Pancasila by applying the Jigsaw type cooperative learning model, as well as the development of PowerPoint media. At the time of implementation, the model teacher was the lead researcher. Meanwhile, members of the research team and PPKn teachers acted as observers. The results of cycle 2 reflection show that the implementation of learning is in accordance with the lesson plan. In class 3, the planning carried out is the reconstruction of the lesson plans for class XI semester I, the main material: Cases of human rights violations in Indonesia by applying a cooperative learning model of a combination of Make Match and Snowball Throwing types, as well as developing PowerPoint, video, and paired cards media. At the implementation stage, the model teacher is the PPKn teacher at the school. Meanwhile, the research team acted as observers. The results of the reflection of cycle 3 show that the implementation of learning is also in accordance with the lesson plan.